From CT to 3D Printed Models, Serious Gaming, and Virtual Reality: Framework for Educational 3D Visualization of Complex Anatomical Spaces From Within—the Pterygopalatine Fossa. - Javan, Ramin; Rao, Aditya; Jeun, Bryan S.; Herur-Raman, Aalap; Singh, Neha; Heidari, Parisa (Journal of Digital Imaging, 2020)
We describe the framework for capturing the internal view of complex anatomical spaces via multiple media and haptic platforms, exemplified by realistic and conceptual representations of the pterygopalatine fossa (PPF). A realistic three-dimensional (3D) mesh of the PPF was developed by segmenting the osseous anatomy on computed tomography (CT) using Materialize InPrint. Subsequently in Autodesk 3D Studio Max, the realistic mesh was enhanced with graphically designed neurovascular anatomy and additionally a conceptual representation of the PPF with its connections and contents was created. An interactive web-compatible Adobe Flash tutorial using ActionScript was developed, allowing users to advance through a series of educational slides that contained interactive rotatable interior camera views and scrollable CT cross-sectional content, incorporating both the realistic and conceptual models. Both models were also 3D printed using polyamide material. In the realistic model, the neurovasculature was colored with water-based acrylic paint. A 3-piece modular design with embedded magnets allows for internal visualization and seamless assembly. A serious gaming environment of the conceptual PPF was also developed using Truevision3D application programming interface, where users can freely move around rooms and hallways that represent various spaces. Lastly, the realistic model was incorporated into a headset-based virtual reality environment, Surgical Theater, allowing visualization and fly-through inside and outside the model. Multiple 3D techniques for visualization of complex 3D anatomical spaces from within were described, with the necessary software and skills detailed. A rough estimate of the time and cost needed to develop these tools as well as multiple supplementary source and end result files are also made available. Educators could utilize multiple advanced delivery methods to incorporate custom digital 3D models of complex anatomical spaces understood from inside.